The use of automated pupillometry to assess cerebral autoregulation: a retrospective study - Quispe Cornejo, Armin; Fernandes Vilarinho, Carla Sofía; Crippa, Ilaria Alice; Peluso, Lorenzo; Calabrò, Lorenzo; Vincent, Jean-Louis; Creteur, Jacques; Taccone, Fabio Silvio (Journal of intensive care, 2020)
Background Critically ill patients are at high risk of developing neurological complications. Among all the potential aetiologies, brain hypoperfusion has been advocated as one of the potential mechanisms. Impairment of cerebral autoregulation (CAR) can result in brain hypoperfusion. However, assessment of CAR is difficult at bedside. We aimed to evaluate whether the automated pupillometer might be able to detect impaired CAR in critically ill patients. Methods We included 92 patients in this retrospective observational study; 52 were septic. CAR was assessed using the Mxa index, which is the correlation index between continuous recording of cerebral blood flow velocities using the transcranial Doppler and invasive arterial blood pressure over 8 ± 2 min. Impaired CAR was defined as an Mxa > 0.3. Automated pupillometer (Neuroptics, Irvine, CA, USA) was used to assess the pupillary light reflex concomitantly to the CAR assessment. Results The median Mxa was 0.33 in the whole cohort (0.33 in septic patients and 0.31 in the non-septic patients; p = 0.77). A total of 51 (55%) patients showed impaired CAR, 28 (54%) in the septic group and 23 (58%) in the non-septic group. We found a statistically significant although weak correlation between Mxa and the Neurologic Pupil Index ( r 2 = 0.04; p = 0.048) in the whole cohort as in septic patients ( r 2 = 0.11; p = 0.026); no correlation was observed in non-septic patients and for other pupillometry-derived variables. Conclusions Automated pupillometry cannot predict CAR indices such as Mxa in a heterogeneous population of critically ill patients.